Scratching the surface? Taxonomic revision of the subgenus Schizoptera (Odontorhagus) reveals vast undocumented biodiversity in the largest litter bug genus Schizoptera Fieber (Hemiptera: Dipsocoromorpha) - Leon, Stephanie; Weirauch, Christiane (Zootaxa, 2016)
Schizoptera Fieber, currently the largest genus of litter bugs (Hemiptera: Dipsocoromorpha), comprises 61 extant species in 4 subgenera. Specimens are abundant in New World bulk and residue samples. Schizoptera species showcase stunning morphology including intricate, asymmetrical genitalia in males that have proven to provide excellent species diagnostic features in the past. Recent bulk sample sorting efforts have revealed a vast number of Schizoptera specimens from across the New World, with the majority representing undescribed species. We here taxonomically revise the subgenus Schizoptera (Odontorhagus) that has recently been shown to form a monophyletic group within Schizoptera. Characterized by the blunt tooth on the posterior margin of the propleuron, Schizoptera (Odontorhagus) previously comprised 10 species from Central and the northern part of South America. We here describe 20 new species in S. (Odontorhagus): S. acuta, n. sp., S. angularis, n. sp., S. ansata, n. sp., S. aspera, n. sp., S. brevis, n. sp., S. dentata, n. sp., S. dolosa, n. sp., S. enigmatica, n. sp., S. exacta, n. sp., S. gorgonensis, n. sp., S. insidiosa, n. sp., S. monstrosa, n. sp., S. piscicaudata, n. sp., S. quasicompleta, n. sp., S. radicata, n. sp., S. serrata, n. sp., S. simpla, n. sp., S. singularis, n. sp., S. trivialis, n. sp., S. ungulata, n. sp., increasing the species count of Schizoptera to 81. We provide morphological documentation including digital habitus images and genitalic drawings for all new species and document and redescribe existing species where feasible. Distribution maps and a key to the species of Schizoptera (Odontorhagus) are also presented. We predict that similar increases in species numbers are to be expected for the remaining subgenera of Schizoptera, making this genus a very diverse lineage of minute litter bugs.